Relationship between Sleep Duration and Stress Level with Menstrual Cycle on Young Women at Senior High School 10 Semarang - Siti Zulaiha Agustina; Rijanto Rijanto; Queen Khoirun Nisa’ Mairo; Evi Pratami (Health Notions, 2022)
During the Covid-19 pandemic, adolescents experienced many things, one of which was a decrease in productivity. Inadolescents, among others, lack of productivity, menstrual disorders, decreased appetite, stress levels and sleep disorders. Factors that affect the menstrual cycle include nutritional status, physical activity, stress levels and sleep duration. The problem in adolescents at this time is the duration of sleep and high levels of stress caused by online learning systems. The data used was the result of filling out the Menstrual Cycle questionnaire, the Pittsburgh Sleep Quality Index (PSQI) and the Depression Anxiety Stress Scales (DASS 42). This research using Chi Square test obtained test results: p-value = 0.038 (there was a relationship between sleep duration and the menstrual cycle). In the stress level research test obtained p-value of 0.005 (there was a relationship between stress levels and the menstrual cycle). It could be concluded that there is a relationship between sleep duration and stress levels with the menstrual cycle in adolescent girls at SMA N 10 Semarang. Keywords: sleep; stress; menstruation; adolescent